(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article examines theater criticism by Yan Michalski (Jornal do Brasil, RJ/1969 and 1970) and Sábato Magaldi (O Estado de São Paulo, SP/1969) on the play As Moças de Isabel Câmara (1967). We analyze how such discourses contributed to the invisibility of the lesbian issue in the work, highlighting the importance of critical reviews to include diverse knowledge. Based on studies of feminist theater and decolonial feminism, we emphasize the relevance of critical fortune in the construction of Brazilian theatrical history and the need for a decentralized approach for an authentic and inclusive understanding of theater, recognizing historically marginalized voices.